Studies on allergy and inflammation - Kay, A. B. (The University of Edinburgh, 1979)
The enclosed papers have been classified into five major sections whose content is as follows:

SECTION A - The eosinophil leucocyte The first works are studies on the mechanisms of eosinophil accumulation following antigen-antibody (1,2 ) reactions in guinea pig skin. ' y These were extended to observations on eosinophil chemotaxis in vitro in relation to the complement system. (3,4)

The eosinophil chemotactic factor of anaphylaxis (ECF-A) was first described in 1971.(5,6) Interactions between ECF-A and complement-derived eosinophilotactic factors were reported later(7) as were investigations on the chemical characterisation of ECF-A.(8) Inhibition of eosinophil chemotaxis by an agent related to disodium cromoglycate is also described.(9) Other eosinophil chemotactic agents thought to participate in eosinophil accumulation in vivo include material derived from Hodgkin's lymph node cells,histamine and one of its major catabolites, imidazole acetic acid.(11) The interactions of these agents both in vitro and in vivo were extensively studied(12,13) and extended to investigations on the response of eosinophils to an ECF-A tetrapeptide and histamine in various disease states(14) as well as the capacity of these agents to mobilise eosinophils in the skin of atopic and non-atopic human volunteers.(15)

Evidence was provided that one of the functions of the eosinophil in allergic tissue reactions may be its capacity to inhibit mast cell 'regranulation'.(16)

Membrane receptors for IgG and complement (C4, C3b and C3d) on human eosinophils and neutrophils and their relation to eosinophilia were described(17) and this work led to the observation that the ECF-A tetrapeptides and histamine both selectively enhance human eosinophil complement receptors.(18)

This work, and those of others, was reviewed in several articles.(19-26)

SECTION B - Mediators of hypersensitivity

In 1974 it was shown that both slow reacting substance of anaphylaxis (SRS-A) and ECF-A were released from passively sensitized skin following interaction with specific antigen.(27) The inactivation of SRS-A by the arylsulphatase contained in various tissues was described(28`) and later it was shown that appreciable amounts of human SRS-A were present in lung as a preformed mediator.(29)

A number of miscellaneous papers relating to mediators are contained in this section: these include an observation on complement activation by Corynebacterium parvum;(30) some chemical and physical properties of synthetic human fibrinopeptides(31) and the description of a primate macrophage-cytophilic antibody(32)

A review of the various biological pathways associated with the inflammatory response as they relate to complications of blood transfusion were described in a review article.(33)

SECTION C - Studies on chemotaxis

This section contains papers on chemotaxis of (34) neutrophils, monocytes and basophils. Particular attention was given to the identification of chemotactic agents associated with Hageman factor-dependent path¬ ways(35), fibrin, formation(36,37) and fibrinolysis.(38,39)

There is a study on the relation between neutrophil accumulation in vivo and agents that are chemotactic in vitro.(40)

Alterations in monocyte chemotaxis in bronchial carcinoma were described.(41)

Much of this work, especially the relation between chemotaxis and haemostasis, was reviewed in 1975.(42)

SECTION D - Clinical studies

This section contains reports on alterations in the complement systems in bronchial asthma(43-45) and the significance of immunoglobulins and complement in pleural effusions associated with bronchial carcinoma.(46) Studies on mediators of hypersensitivity in chronic bronchitis and asthma and their modulation by pharmacological agents are also described.(47,48)

Detailed immunological investigations of two clinical cases, one of chronic benign neutropenia(49) and the other on the effect of transfer factor in chronic mucocutaneous candidiasis,(50) are described.

A consideration of how coagulation and other biological systems may interrelate in the context of 'Stroke' was discussed in a review article.(51)

SECTION E - Methodology

This section contains two articles on methodology, one on the preparation of transfer factor( 52) and the other on tests of immune function.(53)